An Interpretation Approach for in FieldMeasured Dissipation Factor Values of MV Cable Lines - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (11th IEEE International Conference on Solid Dielectrics, 2013)
In modern power utilities attention is especially directed to the condition determination of the network's electrical equipment, with the purpose of supporting the condition oriented asset management and maintenance strategies. In medium voltage (MV) networks, cables require the biggest investment capital. In order to point out the most suitable diagnostic parameters and their limits, a long lasting accelerated and artificial ageing experiment on MV paper insulated lead covered (PILC) cables was performed. The in this way determined dependencies of the diagnostic parameters on voltage, temperature and condition of the cables, as well as characteristic values and regarded failure probability play an immense role in the determination of cables' condition in field measurements. Still, the diagnostic criterion (e.g. in case of dissipation losses comparison of: absolute value, hysteresis, dependency on testing voltage) could significantly influence the final diagnostic statement. In addition, the recorded values have to be evaluated regarding the composition of the cable line. This problematic will be shown in the article and discussed on several exemplar field measurement
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.aninte
Keywords: Power cables; Voltage measurement; Power cable insulation; Correlation coefficient; Dielectrics; Temperature measurement

Comparison of parametric Partial Discharge and Dissipation Factor Characteristics of MV PILC Cables - Mladenovic, Ivana; Weindl, Christian; Freitag, Christian (ISEI, 2012)
Within a long-lasting project, differently pre-aged, as well as brand new medium voltage (MV) paper insulated lead covered cables (PILC) have been artificially aged. Hereby, the dissipation factor and the partial discharges (PD) have been regularly monitored over the complete lifetime of the accelerated aged samples. Additionally, measurement cycles with varied temperatures and voltages have been accomplished in regular time intervals. All measurements were carried out with the network frequency of 50 Hz. In this paper, the results of parametrical studies over a set of predefined voltages (0.4·times nominal voltage up to 2.2·times) and cable temperatures (15°C to 85°C), accomplished under defined and monitored environmental conditions, will be presented and discussed. Additionally, possible correlations of the PD activity and its intensity on the functional characteristic of tan(δ) will be analyzed by the use of three-dimensional parametrical comparison studies. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.compar
Keywords: ageing; cable; diagnostic; dissipation factor; partial discharge

Experiences on in Field Measured Dissipation Factor on MV PILC Cables at 50 Hz - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (22. International Conference on Electricity Distribution CIRED 2013, 2013)
In the past several years, a significant amount of diagnostic data has been collected under known and adjustable test conditions, with the purpose of improving the diagnostic possibilities for medium voltage (MV) paper insulated lead covered (PILC) cables. Beside the complexity of the interpretation processes by itself, an additional challenge of onsite measurements is the investigation of mixed cable lines, as the analysis of the results is proven to be difficult. Moreover, when interpreting the measured values, i.e. diagnostic parameters, the problem often arises that different applied diagnostic criteria (e.g. in case of dissipation losses comparison of: absolute value, hysteresis, dependency on testing voltage) result in different statements. In this paper, empirically determined dependencies of the diagnostic parameter (in front of all the dissipation factor on test conditions) as well as the results of the in-field measured values and suggestion for their interpretation are presented.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.experi
Keywords: field measured dissipation factor; MV PILC cables; diagnostic data collection; medium voltage paper insulated lead covered cable; onsite measurements; mixed cable lines; diagnostic parameter; frequency 50 Hz

Fully Automated MV Cable Monitoring and Measurement System for Multi-Sample Acquisition of Artificial Aging Parameters - Freitag, Christian; Weindl, Christian; Mladenovic, Ivana (International Conference on Renewable Energies and Power Quality ICREPQ '10, 2010)
The Power quality of our networks is influenced by transients, short- and long-duration variations, voltage unbalance, waveform distortions, voltage fluctuations and power frequency variations. These impacts affect the aging rapidity of the electrical equipment and finally the entire electrical network. By partial discharge (PD) and tan(δ) analyses, it is possible to determine the electrical equipment’s condition. The significance of the results depends on the quality of the measurement system and of the data interpretation. Based on these results, a reliable maintenance and investment strategy could be made, and the reliability of the network could be improved. A specially designed aging system for the accelerated aging of MV cables has been developed to point out the most relevant aging parameters and their limits, and, in this way, to upgrade the accuracy of the MV cable diagnostics. In this paper, the system’s “intelligence”, which controls the aging process and acquires, evaluates and stores all necessary data is presente
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.fullya
Keywords: CAMAC (Computer automated measurement and control); Partial discharges; Power cable insulation

New System for Artifical Ageing of MV Cables under Controlled Conditions - Mladenovic, Ivana; Freitag, Christian; Weindl, Christian (20th International Conference and Exhibition on Electricity Distribution CIRED 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.newsys

On-Line Cable Diagnostic Possibilities in an Artificial Aging Environment - Freitag, Christian; Weindl, Christian; Mladenovic, Ivana (International Conference on Renewable Energies and Power Quality ICREPQ, 2011)
Since more than a decade the development of reliable and accurate diagnostic tools for power cables is in the centre of interest of scientists and power utilities. With the developments in our power systems, like the increasing feed-in of renewable energy sources, several issues could be additionally generated, such as extreme concurrence factors, short- and long-duration variations, voltage imbalances, waveform distortions, voltage fluctuations and power frequency variations. These impacts affect the aging rapidity of the electrical equipment and finally of the entire the electrical distribution network. Using appropriate diagnostic methods, it is possible to determine the electrical equipment’s condition. The significance of the results depends on the quality of the measurement system and of the data interpretation. Based on these results, a reliable maintenance and investment strategy could be made, and the reliability of the grid could be improved. With this goal, an accelerated aging project for MV PILC (paper insulated lead covered) cables was started. A specially designed aging system for the accelerated aging of MV cables has been developed to point out the most relevant aging parameters, their limits, their development and to upgrade the accuracy of the MV cable diagnostics in this way. In this paper, the diagnostic possibilities, mainly the dielec- tric loss factor measurement and its dependence on environmental influences are presente
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.online
Keywords: diagnostics; aging; cable; partial discharge; loss factor

Systematische Alterungsuntersuchung an Papier-Masse-isolierten Mittelspannungskabeln - Weindl, Christian; Mladenovic, Ivana; Freitag, Christian (Netzpraxis: Magazin für Energieversorgung - Planung, Bau, Betrieb, Service, 2011)
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.leen.system_2

Verlustfaktormessung an Mittelspannungskabeln bei Netzfrequenz - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (VDE-Kongress: Diagnostik elektrischer Betriebsmittel, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.verlus